2009
DOI: 10.1007/s10552-009-9384-1
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer and reproductive factors among women in Spain

Abstract: Hormonal factors, possibly related to reproductive characteristics, may play a role in the risk of bladder cancer among women. To study this, we investigated the effects of reproductive factors on female bladder cancer risk. Information on reproductive and other risk factors was gathered in personal interviews from 152 female cases and 166 matched controls from 18 hospitals in five regions of Spain during 1998-2001. Logistic regression was used to estimate the association between bladder cancer and reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 27 publications
6
26
3
1
Order By: Relevance
“…Among patients with persistent haematuria, mean parity also did not differ between patients with and without bladder cancer (p=0.38). In contrast to our findings, there are numerous studies suggesting that the risk of bladder cancer is higher in nulliparous women and the risk of bladder cancer decreases with increasing parity (Prizment et al, 2007;Huang et al, 2009). A recent study demonstrated 30% reduction in the risk of bladder cancer in multiparous compared to nulliparous women (Dietrich et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Among patients with persistent haematuria, mean parity also did not differ between patients with and without bladder cancer (p=0.38). In contrast to our findings, there are numerous studies suggesting that the risk of bladder cancer is higher in nulliparous women and the risk of bladder cancer decreases with increasing parity (Prizment et al, 2007;Huang et al, 2009). A recent study demonstrated 30% reduction in the risk of bladder cancer in multiparous compared to nulliparous women (Dietrich et al, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…Although Prizment et al (2007) reported increasing risk of bladder cancer with decreasing ovulatory years in women's life, we did not observe an increased incidence of bladder cancer in postmenopausal period (p=0.30). Our study is limited by the sample size; however, similar to our study, Huang et al (2009) studied the association between bladder cancer and reproductive factors in Spanish women and did not report an increased risk of bladder cancer in association with menopausal status. During menopause, many factors such as obesity, eating habits and androgen levels in peripheral circulation affect the levels of oestrogen derivatives in the circulation (Aubertin-Leheudre et al, 2011).…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations